Intraoperative low-dose dopamine is associated with worse survival in patients with hepatocellular carcinoma: A propensity score matching analysis - Wang, Yan; Xue, Ruifeng; Xing, Wei; Li, Qiang; Gei, Liba; Yan, Fang; Mai, Dongmei; Zeng, Weian; Yan, Yan; Chen, Dongtai (Frontiers in Oncology, 2022)
Background Dopamine is widely used in patients during surgery. We evaluated the association between intraoperative low-dose dopamine administration and recurrence-free survival (RFS) and overall survival (OS) in patients with hepatocellular carcinoma (HCC). Methods Consecutive patients with nonmetastatic HCC who underwent radical hepatectomy were enrolled between 2008 and 2010. Univariate and multivariate logistic regression analyses were used to evaluate the prognostic factors for RFS and OS. Survival outcomes were evaluated using Kaplan–Meier analyses with the log-rank test. A one-to-one propensity score matching (PSM) analysis was performed to reduce confounding bias. Results A total of 805 HCC patients, including 699 patients who did not receive dopamine consumption and 106 patients who received low-dose dopamine during the operation, were retrospectively analyzed. The patients who were assigned low-dose dopamine had worse RFS (p = 0.009) and OS (p = 0.041) than those who did not receive dopamine. Multivariate regression analysis showed that the intraoperative administration of low-dose dopamine was an independent unfavorable predictor for RFS (p = 0.004) but not for OS (p = 0.059). After PSM, the low-dose dopamine-treated group still had significantly poorer RFS (p = 0.003) and OS (p = 0.002). When stratified by time of recurrence, patients with low-dose dopamine use had a significantly greater chance of recurrence within 2 years (p = 0.007) but not after 2 years (p = 0.186). Conclusions Intraoperative low-dose dopamine use has a negative impact on RFS and OS in HCC patients who have undergone radical hepatectomy. Further prospective studies are required to assess the effects of low-dose dopamine on surgical outcomes in HCC patients.